Milk Protein - Hurley, Walter L. (IntechOpen, 2012)
This book provides insights into a wide range of topics related to milk protein. The chapters of this book will be of significant value to those interested in dairy foods, milk chemistry, cheese production, human health, neonatal development, lactation and mammary gland biology, and milk protein production. These chapters explore a range of topics related to milk protein, including: bioactivities of milk proteins and the peptides generated from those proteins; novel functions ascribed for some milk proteins; how processing of milk can impact milk proteins; allergies associated with consumption of milk; genetic variation of milk proteins; application of genomic technologies to explore expression of proteins during milk synthesis; and production of milk and milk protein as affected by environmental factors.